Building critical community Engagement through Scholarship: three case Studies - Findlay, Isobel M.; Lovrod, Marie; Quinlan, Elizabeth; Teucher, Ulrich; Alexander Kiew, Sayok; Stephanie, Bustamante; Domshy, Darlene (University of Saskatchewan, 2015)
Drawing on a shared recognition that community is defined, understood, constructed, and reconstructed through contextually inflected relationships, collaborating authors use diverse interdisciplinary case studies to argue that rigorous communityengaged scholarship advances capacities for critical pursuit of cognitive and social justice. Whether through participant-centred projects undertaken with youth in government care networks, cross-cultural explorations of Indigenous and non-Indigenous science and culture as resources for food security, or facilitated dramatizations of community relations impacted by neo-liberal ideologies, contributors affirm welcoming co-learning environments that engage multiple forms of knowledge expression and mobilization. The respectful spaces held in these community-researcher collaborations enable new advances beyond hegemonic knowledge development institutionalized through colonialist histories. This essay theorizes prospects for building transformative community through scholarship, citing practical examples of the principles and practices that foster or frustrate sustainable communities. It explores the institutional arrangements and power dynamics between and among actors, asking who gets included and excluded, and what boundaries are created and crossed around complex, contradictory, and contested notions of “community.”